Evaluation and spatiotemporal evolution of veterinary talent competitiveness: a new perspective of veterinary education - Xu, Xianhang; Arshad, Mohd Anuar; Jian, Yugang; Mahmood, Arshad; Dong, Mengdie (Frontiers in Veterinary Science, 2024)
IntroductionImproving the quantity and quality of veterinary talent cultivation is an urgent issue to address in current veterinary education and is key to enhancing veterinary talent competitiveness. Starting from an industrial perspective, the introduction of scientific analytical methods for studying veterinary talent competitiveness offers a new view on veterinary education and helps to improve the quality of veterinary education and talent cultivation.MethodsThis study develops a veterinary talent competitiveness evaluation index based on the characteristics of veterinary talent. It proposes a visual method to analyze the level and spatiotemporal evolution of veterinary talent competitiveness using the Entropy method and ArcGIS tools, with Western China as a case study. Data is collected from 12 regions in Western China, spanning 2015 to 2021.ResultsThe results show that the method not only evaluates the current state of veterinary talent competitiveness but also considers temporal and spatial evolution, achieving good evaluation effectiveness and high accuracy, thereby guiding the improvement of veterinary education and talent cultivation.DiscussionBased on the research findings, the study suggests improving the quality of veterinary education and talent cultivation through measures such as strengthening talent resource development, addressing regional imbalances, and promoting spatial integration to achieve a virtuous cycle between veterinary education and industrial development.